Experimental modelling of failure risks using wipe dispenser systems and ready-to-use disinfecting wipes and their consequences - Lüdtke, Wiebke; Zwicker, Paula; Gebel, Jürgen; Exner, Martin; Kramer, Axel (GMS Hygiene and Infection Control)
Introduction: A blinded survey in 81 dental practices, 84 medical practices, and 35 hospitals revealed that for conducting disinfecting surface cleaning and surface disinfection, instead of reusable clothes moistened on-site with disinfectant solution, either wipe dispenser systems for self-preparation or ready-to-use (RTU) wipes are being used. Therefore, the aim of this study was to examine, i.e., the impact of incorrect loading of the wipe roll with disinfectant solution (DS) when using wipe dispenser systems, and the consistency of the DS delivery amount when using RTU wipes. Method: In two different wipe dispenser systems, the saturation of the wipe roll after loading with DS was visually inspected and photographically documented by adding 0.1% fluorescein sodium to the disinfectant solution. The coverage of the wipes used on a melamine resin surface (75x133 cm) was visually checked after a defined wiping mode following analogous staining.